Images and monuments of Near Eastern dynasts 100 BC - AD 100 - Kropp, Andreas Jacob Marwan (Oxford studies in ancient culture and representation, 2013)
This is an archaeological and art-historical study of the images and monuments of Roman 'client' kings in the Near East from the Taurus to Edom (modern South East Turkey, Syria, Lebanon, Israel, Palestine, and Jordan) in the important transitional period between the downfall of the Seleucid empire and ancient Rome's establishment of provincial administration across the entire region. The book treats royal portraits, tombs, palaces, coins, and temples as historical documents and aims at uncovering royal identities and ideological aspirations.